2021
DOI: 10.1111/dom.14285
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of imeglimin in Japanese patients with type 2 diabetes: A 24‐week, randomized, double‐blind, placebo‐controlled, dose‐ranging phase 2b trial

Abstract: Aim To assess the efficacy and safety of imeglimin monotherapy compared with placebo for 24 weeks in Japanese patients with type 2 diabetes (T2D). Materials and Methods In this 24‐week, randomized, double‐blind, placebo‐controlled, parallel‐group, dose‐ranging, phase 2b clinical trial, Japanese adults (age ≥ 20 years) with T2D either treatment‐naïve or previously treated with one oral antidiabetes agent were eligible for participation. Patients were randomly assigned (1:1:1:1) to receive orally imeglimin 500, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(96 citation statements)
references
References 18 publications
10
86
0
Order By: Relevance
“…Detailed studies have shown that this drug may have a positive effect on metabolism by improving glucose and lipid profiles in the context of diabetes 2 , 4 , 5 . Imeglimin is currently under clinical trials around the world and has been reported to improve both blood glucose and glycated hemoglobin (HbA1c) levels and to be safe 4 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies have shown that this drug may have a positive effect on metabolism by improving glucose and lipid profiles in the context of diabetes 2 , 4 , 5 . Imeglimin is currently under clinical trials around the world and has been reported to improve both blood glucose and glycated hemoglobin (HbA1c) levels and to be safe 4 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to lowering A1C, imeglimin has been found to decrease fasting plasma glucose when given at a dose of 1,000 or 1,500 mg twice daily (6)(7)(8)(9). Additionally, discontinuation rates were similar to those occurring with placebo and those of the monotherapy group when studied as an add-on therapy (6)(7)(8)(9), showing further promise for imeglimin as a potential add-on agent. Although its place in diabetes therapy is not yet known, this novel treatment offers a new option for patients and clinicians when trying to optimize glycemic control.…”
Section: Commentarymentioning
confidence: 92%
“…Imeglimin is associated with gastrointestinal adverse reactions such as nausea, abdominal pain, and vomiting. The incidence of gastrointestinal disorders increased as the dose increased and was better tolerated at a dose of 1,000 mg twice daily than at a dose of 1,500 mg twice daily (6). Ongoing and future studies of imeglimin will continue to evaluate and shed light on the tolerability and safety of this agent.…”
Section: Potential Disadvantagesmentioning
confidence: 98%
“…12,13 In a recent larger study that included 299 Japanese adults with diabetes who were treatment naïve or previously treated with only one oral antidiabetic medication, the efficacy and safety profile of imeglimin as a monotherapy was assessed compared with placebo. 14 In this 24-week, randomized, double-blind, parallel group, dose-ranging, phase IIb clinical trial, the participants were randomized (1:1:1:1) to the following: imeglimin 500 mg, imeglimin 1,000 mg, imeglimin 1,500 mg or placebo BID. At week 24, imeglimin considerably reduced HbA1c versus placebo (imeglimin 500 mg versus placebo: -0.52%; imeglimin 1,000 mg versus placebo: -0.94%; imeglimin 1,500 mg versus placebo: -1.00%).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…According to this trial, imeglimin was proven to be well tolerated as a monotherapy, significantly boosting glycaemic control by reducing HbA1c, compared with the placebo. 14 The approval of imeglimin in Japan is supported by a phase III clinical programme, which includes three trials: TIMES 1, TIMES 2 and TIMES 3 (Trials of imeglimin for efficacy and safety). [15][16][17] In TIMES 1, which was a randomized, double-blind, placebo-controlled monotherapy study that included 213 Japanese patients (mean age 62 years) with type 2 diabetes, orally administered imeglimin (1,000 mg BID) was compared with placebo for 24 weeks.…”
Section: Clinical Studiesmentioning
confidence: 99%